DESAIN MODEL BAHAN AJAR BERBASIS ELEKTRONIK DAN MINAT BELAJAR PENDIDIKAN AGAMA ISLAM SISWA SEKOLAH DASAR NEGERI (SDN) KELAS BAWAH DI INDONESIA - Nasir, Muhammad; Alkhury, Saifun Nizar; Rijal, Muhammad Khairul (FENOMENA, 2021)
Abstract Religious learning in the era of information technology development, especially in formal education institutions, faces serious challenges, if the teaching materials used are the majority of printed teaching materials and teacher teaching strategies are more dominant in applying a teacher-centered approach. Thus, in this millennial era, teachers are required to be more creative and innovative in developing and designing teaching materials, media, and student-centered learning strategies to increase motivation and interest in learning. This study aims to design an electronic-based Islamic Religious Education (PAI) teaching material model to increase student interest in elementary school (SDN) in Indonesia. Theories related to this design are the characteristics of the content and teaching materials of Islamic Religious Education, constructivist learning theory, technological and humanistic curricula as well as the characteristics of lower grade Public Elementary School (SDN) students. The type of research used is research and development with data collection techniques, interviews, and observations. The research findings show that the results of limited trials and extensive trials of the design of the electronic-based teaching material model of the development results indicate a significant increase in the learning interest of low-grade Public Elementary School (SDN) students in the subject of Islamic Religious Education (PAI) after the treatment. (µ ≤ 0.05). Key-words: Teaching Materials, Learning Interest, Islamic Religious Education and Elementary School Students for Lower Grade AbstrakPembelajaran agama di era perkembangan teknologi informasi terutama di lembaga pendidikan formal mendapat tantangan serius, jika bahan ajar yang digunakan mayoritas bahan ajar cetak dan strategi mengajar guru lebih dominan menerapkan pendekatan yang terpusat pada guru. Dengan demikian, era milineal ini, guru dituntut lebih kreatif dan inovatif dalam mengembangkan dan mendesain bahan ajar, media dan strategi pembelajaran yang terpusat pada siswa untuk meningkatkan motivasi dan minat belajar. Penelitian ini bertujuan mendesain sebuah model bahan ajar Pendidikan Agama Islam (PAI) berbasis elektronik untuk meningkatkan minat belajar Siswa Sekolah Dasar (SDN) di Indoneia. Teori terkait dengan desain ini adalah karakteristk isi dan bahan ajar Pendidikan Agama Islam, teori belajar konstrukvistik, kurikulum teknologis dan humanistik serta karakteristik siswa Sekolah Dasar Negeri (SDN) kelas bawah. Jenis penelitian yang digunakan adalah penelitian dan pengembangan dengan teknik pengumpulan data wawancara, dan observasi. Temuan penelitian memperlihatkan bahwa hasil uji coba terbatas dan uji coba luas atas desain model bahan ajar berbasis elektronik hasil pengembangan menunjukkan adanya peningkatan signifikan minat belajar siswa Sekolah Dasar Negeri (SDN) kelas rendah dalam mata pelajaran Pendidikan Agama Islam (PAI) setelah perlakuan. (µ ≤ 0,05). Key-words: Bahan Ajar, Minat Belajar, Pendidikan Agama Islam  dan Siswa Sekolah Dasar Kelas  Bawah